Concentration of Cd, Pb, Hg, and Se in Different Parts of Human Breast Cancer Tissues - Mehrnoosh Mohammadi; Alireza Riyahi Bakhtiari; Saber Khodabandeh (Journal of Toxicology)
Breast cancer is the major cause of cancer morbidity and mortality between women in the world. Metals involved in environmental toxicology are closely related to tumor growth and cancer. On the other hand, some metals such as selenium have anticarcinogenic properties. The aim of this study is to determine the concentration of cadmium, lead, mercury, and selenium in separated parts of tegmen, tumor, tumor adiposity, and tegmen adiposity of 14 breast cancer tissues which have been analyzed by graphite furnace atomic absorption (AA-670) and ICP-OES (ULTIMA 2CE). Our results show that Se and Hg have maximum and minimum concentration, respectively. Statistical analysis reveals no significant differences between metal accumulations in different parts of cancer tissues (P>0.05) and this observation might be due to the close relation of separated parts of fatty breast organ. Thus, we could conclude that a high level of these heavy metals is accumulated in Iranian cancerous breasts and their presence can be one of the reasons of cancer appearance.